Laminated structure, electronic device, electronic equipment and system

A crystalline metal oxide with superelastic properties is developed, addressing the limitations of conventional shape memory materials by providing excellent corrosion resistance and shape memory effects, suitable for advanced electronic devices.

JP7659927B2Active Publication Date: 2025-04-10GAIANIXX INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023576971
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-01-26
Publication Date
2025-04-10
Estimated Expiration
2043-01-26

AI Technical Summary

Technical Problem

Conventional shape memory materials face issues such as oxidation deterioration and temperature dependence, and there is a need for materials with excellent corrosion resistance and shape memory properties.

Method used

The development of a crystal made of a crystalline metal compound, specifically a metal oxide, which exhibits superelasticity of 10% or more when deformed at or above the transformation temperature, and a manufacturing method involving the formation of a compound film on a crystal substrate followed by epitaxial film lamination.

Benefits of technology

The resulting shape memory material and laminated structure demonstrate excellent corrosion resistance and shape memory properties, enabling the production of advanced electronic devices with improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659927000001
    Figure 0007659927000001
  • Figure 0007659927000002
    Figure 0007659927000002
  • Figure 0007659927000003
    Figure 0007659927000003
Patent Text Reader

Abstract

[Problem] To provide: a crystal having excellent shape memory properties and corrosion resistance; a multilayer structure, an electronic device and an electronic instrument each containing the crystal; and methods respectively for producing these products in an industrially advantageous manner. [Solution] At least an oxide film is formed on a crystal substrate, then an epitaxial film containing a crystalline compound is laminated on the oxide film, and then a second epitaxial film that has a different chemical composition from that in the aforementioned epitaxial film is laminated on the aforementioned epitaxial film directly or with another layer interposed therebetween. In this procedure, the lamination of the epitaxial film is performed by forming the epitaxial film using a compound element in the compound layer. In this manner, an epitaxial film containing a crystal showing a hyperelasticity of 10% or more is formed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crystal, a layered structure, an electronic device, an electronic apparatus, and a method for manufacturing these. [Background technology]

[0002] Conventionally, shape memory materials (also called superelastic materials) exhibiting a shape memory phenomenon or a superelastic phenomenon (also called a pseudoelastic phenomenon) have been known, and their practical application is being promoted in various industrial and medical fields to utilize their unique functions. Shape memory materials include shape memory alloys (SMA) and shape memory polymers (SMPs). As SMAs, for example, Nitinol, an alloy of nickel and titanium, is known (Patent Document 1). Nitinol has excellent shape memory effects and superelastic properties, and is used in medical guide wires, glasses, and the like. As SMPs, 1) polyurethane-based shape memory polymers having ionic or mesogenic components, 2) polyethylene terephthalate-polyethylene oxide (PET-PEO) block copolymers crosslinked with maleic anhydride, and the like are known.

[0003] However, conventional shape memory materials have problems such as oxidation degradation and temperature dependency. In recent years, in order to solve these problems, shape memory materials with oxidation resistance have been investigated (e.g., Patent Document 2, etc.), but they are still not satisfactory, and there has been a long awaited shape memory material with excellent corrosion resistance, including oxidation resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-097790 A [Patent Document 2] International Publication No. WO2018-047787 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a crystal having excellent shape memory properties and corrosion resistance, a laminate structure containing the crystal, an electronic device, an electronic instrument, and a manufacturing method by which these can be obtained in an industrially advantageous manner. [Means for solving the problem]

[0006] As a result of intensive research to achieve the above-mentioned object, the present inventors have found that when at least a compound film is formed on a crystal substrate, an epitaxial film containing a crystalline compound is then laminated, and a second epitaxial film having a composition different from that of the epitaxial film is laminated on the epitaxial film directly or via another layer, the epitaxial film is formed by using a compound element in the compound film to form the epitaxial film, and a regular transformation matching the lattice constant of the second epitaxial film occurs without dislocation or slip deformation, and the epitaxial film exhibits a shape memory phenomenon or a superelastic phenomenon despite being an epitaxial film made of an oxide, and have found that such an epitaxial film is a new shape memory material that can solve the above-mentioned conventional problems at once. After obtaining the above findings, the present inventors conducted further studies and completed the present invention.

[0007] That is, the present invention relates to the following inventions. [1] A crystal made of a crystalline metal compound, characterized in that it exhibits superelasticity of 10% or more when deformed at or above its transformation temperature. [2] The crystal according to [1], wherein the crystalline metal compound is a crystalline metal oxide. [3] The crystal according to [1] or [2], wherein the crystalline metal compound contains Hf. [4] The crystal according to any one of [1] to [3], wherein the crystalline metal compound contains, among its constituent metals, 50 atomic % or more of Hf and / or Zr, and 0.1 atomic % to 50 atomic % of one or more metals selected from Al, Ti, Y and Ce. [5] The crystal according to any one of [1] to [4] above, having a transformation temperature of 350°C to 1000°C. [6] The crystal according to any one of [1] to [5] above, which is a film-like shape-memory material. [7] A method for manufacturing a laminated structure, which comprises forming at least a compound film on a crystal substrate, and then laminating an epitaxial film containing a crystalline compound, characterized in that the epitaxial film is formed by using a compound element in the compound film to form the epitaxial film, thereby forming the epitaxial film containing crystals that exhibit superelasticity of 10% or more by deforming at or above a transformation temperature. [8] The manufacturing method according to [7], further comprising the steps of: using the compound element in the compound film; introducing a compound element gas; and depositing the epitaxial film in the presence of the compound element gas. [9] A laminated structure including at least a crystal substrate and an epitaxial film, the epitaxial film including a shape memory material made of a crystalline metal compound.

[10] The layered structure according to [9], wherein the epitaxial film constitutes a part or the whole of a buffer layer and is a substrate for crystal growth.

[11] A piezoelectric element including a laminated structure, characterized in that the laminated structure is the laminated structure according to [9] or

[10] above.

[12] A method for manufacturing a piezoelectric element using a laminated structure, characterized in that the laminated structure is the laminated structure described in [9] or

[10] above.

[13] An electronic device including a laminated structure, characterized in that the laminated structure is the laminated structure described in [9] or

[10] above.

[14] The electronic device according to

[13] , which is a piezoelectric device.

[15] A method for producing an electronic device using a laminated structure, characterized in that the laminated structure is the laminated structure described in [9] or

[10] above.

[16] An electronic device including an electronic device, the electronic device being the electronic device described in

[14] or

[15] .

[17] A method for manufacturing an electronic device using a laminated structure or an electronic device, characterized in that the laminated structure is the laminated structure described in [9] or

[10] above, and the electronic device is the electronic device described in

[14] or

[15] above.

[18] A system including an electronic device, characterized in that the electronic device is the electronic device described in

[16] .

[19] The laminate structure according to [9], further comprising, between the crystal substrate and the epitaxial film, one or more embedded layers each containing a constituent metal of the epitaxial film and / or the crystal substrate and / or a buried layer each containing the constituent metal embedded in a portion of the crystal substrate.

[20] The laminate structure according to

[19] , further comprising, between the crystal substrate and the epitaxial film, one or more amorphous thin films containing a constituent metal of the epitaxial film and / or one or more buried layers embedded in a portion of the crystal substrate and containing a constituent metal of the epitaxial film.

[21] The laminate structure according to

[19] , further comprising an amorphous thin film between the crystal substrate and the epitaxial film, the amorphous thin film containing a constituent metal of the epitaxial film and / or the crystal substrate, and one or more embedded layers containing the constituent metal embedded in a portion of the crystal substrate.

[22] The laminate structure according to any one of

[19] to

[21] , wherein the constituent metal comprises Hf.

[23] The laminate structure according to any one of

[19] to

[22] , wherein the amorphous thin film has a thickness of 1 nm to 10 nm.

[24] The multilayer structure according to any one of

[19] to

[23] , wherein the embedded layer has a cross-sectional shape of a substantially inverted triangle.

[25] An electronic device, an electronic equipment, or a system including a laminate structure, characterized in that the laminate structure is the laminate structure according to any one of

[19] to

[24] above. Effect of the Invention

[0008] The shape memory material, laminated structure, electronic device, and electronic equipment of the present invention contain an epitaxial film having excellent corrosion resistance, and the manufacturing method of the present invention has the effect of making it possible to obtain the shape memory material, the laminated structure, the electronic device, and the electronic equipment in an industrially advantageous manner. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of an example of a preferred embodiment of a laminated structure of the present invention. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of another preferred embodiment of the laminated structure of the present invention. [Diagram 3] 1A to 1C are diagrams illustrating an example of an oxide film forming step in a preferred method for producing a laminated structure of the present invention. [Figure 4] 1A to 1C are diagrams illustrating an example of an epitaxial film formation step in a preferred method for producing a laminated structure of the present invention. [Diagram 5] 1 shows cross-sectional STEM images observed in the examples. [Figure 6] 1 shows cross-sectional STEM images observed in the examples. [Figure 7] 1 shows STEM images observed in the examples. [Figure 8] 1 shows STEM images observed in the examples. [Figure 9] 1 is a diagram illustrating a preferred embodiment of a MEMS transducer according to the present invention. [Figure 10] FIG. 1 is a schematic diagram showing an example of a cross-sectional view of a portion of a wafer provided with a piezoelectric actuator, as a suitable application example of the present invention to a fluid discharge device. [Figure 11] 1 shows cross-sectional STEM images observed in the examples, where (b) shows a bright field (BF) STEM image of (a). [Figure 12] FIG. 1 is a diagram showing the results of XRD measurement showing the symmetry of crystals in an example. [Figure 13] FIG. 1 is a diagram showing the results of XRD measurement showing the symmetry of crystals in an example. [Figure 14] FIG. 2 is a schematic diagram showing a film forming apparatus preferably used in the examples. [Figure 15] 1 shows a cross-sectional STEM image measured in an example. [Figure 16] 1 shows a STEM image measured in an example. [Figure 17] 1 shows a STEM image of a buried layer measured in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The crystal of the present invention is a crystal made of a crystalline metal compound, preferably a crystalline metal oxide, characterized in that it exhibits a superelasticity of 10% or more by being deformed at a transformation temperature or higher. The crystalline compound is not particularly limited and may be a known crystalline compound, but in the present invention, the crystalline compound is preferably a metal compound, and the metal of the metal compound may also be a known metal. Examples of the metal include metals containing d-block elements in the periodic table. The compound of the metal compound may also be a known compound, and examples of the compound in the crystalline compound include oxides, nitrides, oxynitrides, sulfides, oxysulfides, borides, oxyborides, carbides, oxycarbides, borocarbides, boronitrides, borosulfides, carbonitrides, carbosulfides, and carboborides. In the present invention, oxides or nitrides are preferable because, for example, they can provide better stress relaxation and warpage reduction in heteroepitaxial growth as a buffer layer, and further provide better electrical properties (particularly the interface between the conductor layer and the insulating layer). Moreover, the crystalline compound is preferably a crystalline oxide, the compound film is preferably an oxide film, and the compound element is preferably oxygen. In the present invention, the crystalline compound is preferably a crystalline nitride, the compound film is preferably a nitride film, and the compound element is preferably nitrogen. The crystal may be a single crystal or a polycrystal, but in the present invention, it is preferably a single crystal. In the present invention, the crystal is preferably a film-like shape memory material. A "shape memory material" usually refers to a material that recovers to its original shape before deformation by heating to a predetermined temperature or higher even if it is deformed at a temperature lower than a predetermined temperature, but in the present invention, it is sufficient that a part or all of the shape memory material can be deformed and recover its shape at or above its transformation temperature, and also includes a superelastic material having superelastic properties. The superelastic property means a property that the shape memory material recovers to its original shape by removing the load even if it is deformed (including bending, tension, compression, etc.) at a use temperature above the transformation temperature.In the present invention, the shape-memory material is preferably a shape-memory material having a transformation temperature of 350°C or higher, more preferably 350°C to 1000°C, and most preferably 350°C to 750°C.

[0011] In the present invention, the crystal is preferably a single-layer crystal film including a first crystal face and a second crystal face on the opposite side of the first crystal face, and the first crystal face is regularly transformed to have a constant lattice constant different from that of the second crystal face, and the transformation is more preferably a transformation in which the shape is transformed into a mountain-valley structure. In addition, in the present invention, it is preferable that the angles formed by the adjacent vertices and bottoms of the mountain-valley structure are different, and it is also preferable that the lattice constant difference between the first crystal face and the second crystal face is within a range of 0.1% to 20%. According to such a preferable range, it can be suitably used as a better buffer layer, and not only can the adhesion between the crystal film and a substrate or a crystal film of a different composition provided on the crystal film by crystal growth and the crystallinity of the crystal film be improved, but also the properties of the crystal film as a functional film can be improved.

[0012] In the present invention, the crystal film preferably contains one or more d-block elements, and also preferably contains a metal oxide containing one or more metals selected from the d-block elements of the periodic table. The metal oxide is not particularly limited as long as it does not impede the object of the present invention, but is preferably a metal oxide containing one or more metals selected from Groups 3, 4, and 13 of the periodic table, and more preferably a metal oxide containing one or more metals selected from Group 4 of the periodic table. More specifically, the metal oxide is preferably a crystalline metal oxide, and the crystalline metal oxide preferably contains Hf and / or Zr, and more preferably contains Hf. The crystalline metal oxide may contain other metals than Hf and Zr. When the crystalline metal oxide contains the other metals, the crystalline oxide preferably contains 50 atomic % or more of Hf and / or Zr, and 0.1 atomic % to 50 atomic % of one or more metals selected from Al, Ti, Y and Ce among the constituent metals. In this preferred range, the crystal exhibiting 10% or more of superelasticity can be obtained more easily. In the present invention, in this preferred range, the crystal growth can be made easier and of higher quality, especially as a buffer layer. The crystal structure of the crystalline film is not particularly limited, but it is preferable that the crystalline film has a cubic crystal structure. The crystalline film is preferably a single crystal film containing a crystalline oxide, and is also preferably an epitaxial film.

[0013] The laminated structure of the present invention is a laminated structure including at least an epitaxial film, characterized in that the epitaxial film contains crystals that exhibit superelasticity of 10% or more by being deformed at a transformation temperature or higher. The method for producing the laminated structure is not particularly limited, but is preferably a method for producing a laminated structure by forming at least a compound film on a crystal substrate, and then laminating an epitaxial film containing a crystalline oxide, in which the epitaxial film is formed by using a compound element in the compound film to form the epitaxial film, and the epitaxial film contains crystals that exhibit superelasticity of 10% or more by deforming at a transformation temperature or higher, and such a production method is also included in the present invention.

[0014] Preferred embodiments of the present invention will now be described with reference to the drawings, but the present invention is not limited to these preferred embodiments. Fig. 1 shows a preferred example of the laminated structure, in which an epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film 2, and a second epitaxial layer 4 is further laminated on the epitaxial layer 3. In this specification, the terms "film" and "layer" may be interchanged depending on the case or situation. In addition, oxides are given as preferred examples of the laminated structure, but the present invention is not limited to these preferred examples, and the present invention can also be suitably applied to various compounds such as nitrides. The laminated structure can be easily manufactured, for example, as shown in Fig. 3, by forming an oxide film 2 of the crystal substrate 1 on the crystal substrate 1, and then forming an epitaxial film 3 made of a crystalline oxide on the crystal substrate 1 using oxygen in the oxide film 2 as shown in Fig. 4, and then forming the second epitaxial film on the epitaxial film 3. In the present invention, the laminated structure may have the oxide film 2 on the crystal substrate 1, but the oxide film 2 may disappear when all the oxygen in the oxide film 2 is taken in during the formation of the epitaxial film 3. Each of these will be described in more detail below, but the present invention is not limited to these specific examples.

[0015] The crystal substrate (hereinafter, simply referred to as "substrate") is not particularly limited as long as the object of the present invention is not hindered, such as the substrate material, and may be a known crystal substrate. It may be an organic compound or an inorganic compound. In the present invention, it is preferable that the crystal substrate contains an inorganic compound. In the present invention, it is preferable that the substrate has crystals on a part or all of the surface, more preferably a crystal substrate having crystals on all or a part of the main surface on the crystal growth side, and most preferably a crystal substrate having crystals on the entire main surface on the crystal growth side. The crystal is not particularly limited as long as the object of the present invention is not hindered, and the crystal structure is not particularly limited, but it is preferable that it is a cubic, tetragonal, trigonal, hexagonal, orthorhombic, or monoclinic crystal, and more preferably a crystal oriented in (100) or (200). In addition, the crystal substrate may have an off angle, and examples of the off angle include an off angle of 0.2° to 12.0°. Here, the "off angle" refers to the angle between the substrate surface and the crystal growth surface. The shape of the substrate is not particularly limited as long as it is plate-like and serves as a support for the epitaxial film. It may be an insulating substrate or a semiconductor substrate, but in the present invention, the substrate is preferably a Si substrate, more preferably a crystalline Si substrate, and most preferably a crystalline Si substrate oriented in (100). In addition to the Si substrate, examples of the substrate material include one or more metals belonging to Groups 3 to 15 of the periodic table or oxides of these metals. The shape of the substrate is not particularly limited, and may be an approximately circular shape (e.g., a circular shape, an elliptical shape, etc.) or a polygonal shape (e.g., a triangular shape, a square shape, a rectangular shape, a pentagonal shape, a hexagonal shape, a heptagonal shape, an octagonal shape, a nonagonal shape, etc.), and various shapes can be suitably used. In addition, in the present invention, a large-area substrate can be used, and the area of ​​the epitaxial film can be increased by using such a large-area substrate.

[0016] In the present invention, the crystal substrate preferably has a flat surface, but it is also preferable that the crystal substrate has an uneven shape on a part or all of the surface, since this can improve the quality of the crystal growth of the epitaxial film. The crystal substrate having the uneven shape may have an uneven portion consisting of a concave or convex portion formed on a part or all of the surface, and the uneven portion is not particularly limited as long as it is composed of a convex portion or a concave portion, and may be an uneven portion consisting of a convex portion, an uneven portion consisting of a concave portion, or an uneven portion consisting of a convex portion and a concave portion. The uneven portion may be formed of regular convex portions or concave portions, or may be formed of irregular convex portions or concave portions. In the present invention, it is preferable that the uneven portion is formed periodically, and it is more preferable that the uneven portion is patterned periodically and regularly. The shape of the uneven portion is not particularly limited, and examples thereof include a stripe shape, a dot shape, a mesh shape, and a random shape, but in the present invention, a dot shape or a stripe shape is preferable, and a dot shape is more preferable. In addition, when the unevenness is patterned periodically and regularly, the pattern shape of the unevenness is preferably a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon, a circle, or an ellipse. In addition, when the unevenness is formed in a dot shape, the lattice shape of the dots is preferably a lattice shape such as a square lattice, an oblique lattice, a triangular lattice, or a hexagonal lattice, and more preferably a triangular lattice shape. The cross-sectional shape of the concave or convex part of the unevenness is not particularly limited, but examples thereof include a U-shape, a U-shape, an inverted U-shape, a wave shape, or a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon. In addition, the thickness of the crystal substrate is not particularly limited, but is preferably 50 to 2000 μm, and more preferably 100 to 1000 μm.

[0017] The oxide film is not particularly limited as long as it is an oxide film capable of incorporating oxygen atoms into the epitaxial film, and usually includes an oxide material. The oxide material is not particularly limited as long as it does not impede the object of the present invention, and may be a known oxide material. Examples of the oxide material include oxides of metals or semimetals. In the present invention, it is preferable that the oxide film includes the oxide material of the crystal substrate, and examples of such oxide films include a thermal oxide film and a natural oxide film of the crystal substrate. In addition, in the present invention, the oxide film may be a sacrificial layer in which a part or all of the film disappears or is destroyed when oxygen atoms are incorporated, and in the present invention, it is preferable that the oxide film is an oxygen supply sacrificial layer in which oxygen atoms are incorporated and the oxide film itself disappears during the crystal growth of the epitaxial layer. In addition, the oxide film may be patterned, for example, in a striped, dotted, meshed, or random pattern. The thickness of the oxide film is not particularly limited, but is preferably more than 1 nm and less than 100 nm.

[0018] The epitaxial layer preferably includes an epitaxial film incorporating oxygen atoms from the oxide film. The phrase "epitaxial film incorporating oxygen atoms from the oxide film" means that oxygen atoms from the oxide film are taken by the epitaxial film during the crystal growth of the epitaxial film. The epitaxial film is not particularly limited as long as it is an epitaxial film that has been crystal-grown by incorporating oxygen atoms from the oxide film, but in the present invention, it is preferable that the epitaxial film includes a metal or a metal oxide. The metal is preferably, for example, one or more metals belonging to the d block of the periodic table. The metal oxide is preferably, for example, one or more oxides of metals belonging to the d block of the periodic table. In the present invention, the epitaxial film preferably includes a dielectric. In addition, in the present invention, the epitaxial film preferably includes a neutron absorbing material. The neutron absorber may be a known neutron absorber, and in the present invention, by using such a neutron absorber to capture oxygen from the oxide film, it is possible to improve adhesion, crystallinity, and further the properties of the functional film. A suitable example of the neutron absorber is hafnium (Hf). The epitaxial layer may be composed of one or more types of epitaxial films, and in the present invention, it is preferable that the epitaxial layer includes two or more types of the epitaxial films. More specifically, for example, it is preferable that a second epitaxial film having a composition different from that of the epitaxial film is laminated on the epitaxial film directly or via another layer. By stacking in this manner, the first epitaxial layer can be regularly transformed at the interface between the epitaxial layer (hereinafter also referred to as the "first epitaxial layer") and the second epitaxial layer so that the lattice constant thereof becomes approximately the same as that of the second epitaxial layer.As a preferred example of the regular transformation, for example, a transformation in which the shape is transformed into a mountain-valley structure is given. In the present invention, it is preferable that the angles formed by the adjacent vertices and bottoms of the mountain-valley structure are different from each other, and it is more preferable that each of the angles is within the range of 30° to 45°. Here, the epitaxial layer usually has a first crystal face and a second crystal face, and since the transformation may cause a lattice constant difference between the first crystal face and the second crystal face, it is preferable that the lattice constant difference between the first crystal face and the second crystal face is within the range of 0.1% to 20%. In the present invention, since the first crystal face can be made substantially the same as the lattice constant of the second epitaxial film, it is easy to realize that the lattice constant difference between the first epitaxial layer and the second epitaxial layer is within the range of 0.1% to 20%.

[0019] In the present invention, it is more preferable that the epitaxial film is a dielectric and the second epitaxial film is an electrode. By using the second epitaxial layer as an electrode, not only can the adhesion and crystallinity at the interface be improved, but also, for example, the characteristics of the element can be improved. In addition, according to the present invention, when the second epitaxial layer is made of a single crystal film of a conductive metal, a large-area defect-free film can be easily obtained, and not only the function as an electrode but also the characteristics of the element can be improved. The conductive metal is not particularly limited as long as it does not impede the object of the present invention, and examples thereof include gold, silver, platinum, palladium, silver-palladium, copper, nickel, and alloys thereof, but in the present invention, it is preferable that it contains platinum. In addition, in the present invention, according to the above-mentioned manufacturing method, it is preferable to obtain a film having a thickness of 100 nm or more. 2 A defect-free single crystal film can be obtained as an electrode with an area of ​​1000 nm or more. 2 A defect-free single crystal film can be easily obtained with the above area. Also, a single crystal film having a thickness of preferably 100 nm or more can be easily obtained as an electrode.

[0020] In the present invention, it is preferable that a third epitaxial film and / or a fourth epitaxial film having a composition different from that of the second epitaxial film is laminated on the second epitaxial film directly or via another layer. Fig. 2 shows a preferred example of a laminated structure in which the third epitaxial layer 5 and the fourth epitaxial layer 6 are laminated on the second epitaxial layer 4. In the laminated structure of Fig. 2, a first epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film, and further, a second epitaxial layer 4 is laminated on the first epitaxial layer 3, a third epitaxial layer 5 is laminated on the second epitaxial layer 4, and a fourth epitaxial layer 6 is laminated on the third epitaxial layer 5. The third epitaxial film in the third epitaxial layer is preferably a dielectric, a semiconductor or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The fourth epitaxial film in the fourth epitaxial layer is preferably a dielectric, a semiconductor or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The thickness of each of the epitaxial films is not particularly limited, but is preferably 10 nm to 100 μm, and more preferably 50 nm to 30 μm.

[0021] The laminated structure can be easily obtained by forming an epitaxial film using oxygen atoms in the oxide film at 350° C. to 700° C. in a method for manufacturing a laminated structure in which an epitaxial layer is laminated on a crystal substrate via at least an oxide film, and the lamination is performed at 350° C. to 700° C. If the temperature is within the range of 350° C. to 700° C., the oxygen atoms in the oxide film can be easily incorporated into the epitaxial film to cause crystal growth.

[0022] In the present invention, it is preferable to form the epitaxial film by using oxygen gas after using oxygen atoms in the oxide film, and the film formation rate is improved by forming the epitaxial film in this manner. Also, by forming the film in this manner, a laminated structure in which an epitaxial layer is laminated on a crystal substrate, and a laminated structure having an amorphous thin film containing a constituent metal of the epitaxial layer and / or the crystal substrate and / or a buried layer containing the constituent metal and embedded in a part of the crystal substrate, which is one or more, can be easily obtained. In the present invention, it is preferable that the laminated structure has both the amorphous layer and the buried layer, since the functionality of the epitaxial film can be further improved. Also, it is preferable that the amorphous layer and the buried layer each contain a constituent metal of the epitaxial layer, since the crystallinity of the epitaxial film is further improved. In the present invention, it is preferable that the constituent metal contains Hf, since this further promotes stress relaxation and further enables stress relaxation in multiple stages. In the present invention, it is preferable that the amorphous thin film has a thickness of 1 nm to 10 nm, since this can further improve the crystallinity of the epitaxial film, and an amorphous thin film having such a preferable thickness can be easily obtained by the preferred manufacturing method of the present invention. In the present invention, it is preferable that the buried layer has a cross-sectional shape of an approximately inverted triangle, since this can further improve the functionality of the epitaxial film. These preferable laminated structures can be easily obtained by appropriately adjusting the thickness of the oxide film and the timing of introducing the oxygen gas.

[0023] As the lamination means used in the lamination, the deposition means for the epitaxial film is usually preferably used, and the deposition means may be a known deposition means. In the present invention, the deposition means is preferably vapor deposition or sputtering, and more preferably vapor deposition.

[0024] The crystal film or laminated structure obtained as described above is suitably used in electronic devices according to a conventional method. For example, the laminated structure can be connected to a power source or an electric / electronic circuit as a piezoelectric element, and mounted on a circuit board or packaged to form various electronic devices. In the present invention, the electronic device is preferably a piezoelectric device, and can be used as a piezoelectric device in electronic devices such as inkjet printer heads, microactuators, gyroscopes, and motion sensors. In addition, for example, if an amplifier and a rectifier circuit are connected and packaged, it can be used in various sensors such as magnetic sensors. It can also be applied to constant voltage driven memories, and for example, if a storage element and a rectifier power management circuit are connected, it becomes an energy conversion device (energy harvester) that generates power from an external magnetic field or vibration. The energy conversion device is incorporated and used in power supply systems and wearable terminals (earphones / hearable devices, smart watches, smart glasses (eyeglasses), smart contact lenses, cochlear implants, cardiac pacemakers, etc.). In the present invention, the laminated structure is preferably used in, for example, smart glasses, AR headsets, MEMS mirrors for LiDAR systems, piezoelectric MEMS ultrasonic transducers (PMUTs) for advanced medical applications, and piezo heads for commercial and industrial 3D printers.

[0025] The electronic device is suitably used in electronic devices in the usual manner, and can be applied to various electronic devices other than the above-mentioned electronic devices, and more specifically, suitable examples include liquid ejection heads, liquid ejection devices, vibration wave motors, optical devices, vibration devices, imaging devices, piezoelectric acoustic parts, audio playback devices having the piezoelectric acoustic parts, audio recording devices, mobile phones, various information terminals, and the like.

[0026] Furthermore, the electronic device is also applied to a system in the usual manner, and an example of such a system is a sensor system. EXAMPLES

[0027] Example 1 The crystal growth surface side of the Si substrate (100) was treated by RIE, and then heated in the presence of oxygen to form a thermal oxide film. Then, without using oxygen, a metal from the deposition source was thermally reacted with oxygen in the oxide film on the Si substrate by a deposition method to form a single crystal of a crystalline metal oxide on the Si substrate. Next, oxygen was introduced, the temperature was lowered, and the pressure was increased, and a single crystal film of a crystalline metal oxide was formed as the crystal by a deposition method. The deposition conditions during this film formation were as follows: Vapor deposition source: Hf, Zr Voltage: 3.5~4.75V Pressure: 3×10 -2 ~6×10 -2 Pa Substrate temperature: 450~700℃

[0028] Next, a platinum (Pt) metal film was formed as a conductive film on the single crystal film of the crystalline metal oxide by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Pressure: 1.20×10 -1 Pa Target: Pt Power: 100W(DC) Thickness: 100nm Substrate temperature: 450~600℃

[0029] Next, an SRO film was formed on the conductive film by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Power: 150W(RF) Gas: Ar Pressure: 1.8Pa Substrate temperature: 600℃ Thickness: 20nm

[0030] Next, a Pb(Zr 0.52 Ti 0.48 The conditions for this are as follows:

[0031] Lead acetate was used as the raw material for Pb, zirconyl nitrate was used as the raw material for Zr, and titanium isopropoxide was used as the raw material for Ti. The raw materials for Pb, Zr, and Ti were mixed to a composition ratio of Pb:Zr:Ti=100+δ:52:48, and the solvent was pure water in consideration of the solubility of the raw materials, with acetic acid added to control hydrolysis. Furthermore, ethanol (0.5-3.0 mol per 1 mol of PZT) in which polyvinylpyrrolidone powder had been mixed and dissolved was added to adjust the viscosity. Finally, an appropriate amount of 2n-butoxyethanol was mixed to adjust the wettability during application, and a sol-gel solution was prepared as the raw material solution.

[0032] Next, the prepared sol-gel solution was dropped onto a substrate and rotated at 2000 rpm for 1 minute to spin coat (apply) the sol-gel solution onto the substrate to form a film containing the precursor. The substrate was then placed on a hot plate at 150°C, and then placed on a hot plate at 350°C to evaporate the solvent and dry the film. This process was repeated five times to stack five layers under the same conditions, and then the precursor was oxidized and crystallized by heat treatment at 650°C for 3 minutes in an oxygen (O2) atmosphere. The above process was repeated 10 times to obtain Pb(Zr 0.52 Ti 0.48 The total thickness of the film was 10 μm.

[0033] The obtained laminated structure was a laminated structure including an epitaxial film having good adhesion and crystallinity. In addition, cross-sectional STEM images of the obtained laminated structure are shown in Figs. 5 and 6. It can be seen from Fig. 6 that a very good laminated structure was obtained, and in particular, in Fig. 5, it can be seen that a regular mountain-valley structure is provided at the interface between the single crystal film of the crystalline metal oxide and the conductive film, and the angles formed by the adjacent vertices and bottom points of the mountain-valley structure are different within the range of 30° to 45°. In addition, X-ray crystal lattice images of the conductive film are shown in Figs. 7 and 8. From Figs. 7 and 8, it can be seen that a defect-free large-area conductive film is obtained, and it can be seen that excellent effects are exhibited in terms of electrode characteristics and the piezoelectric characteristics of the piezoelectric film laminated thereon. Conventionally, it has been difficult for a piezoelectric film formed by spin coating to exhibit piezoelectric characteristics, but the piezoelectric film (PZT film) formed by spin coating in this embodiment had good piezoelectric characteristics. In addition, the crystals of the crystal substrate of the laminated structure, the single crystal film of the crystalline metal oxide, and the conductive film were measured using an X-ray diffraction device. The results of the XRD measurements are shown in Figure 12. As is clear from Figure 12, a (Hf, Zr)O2 film and a Pt single crystal film having good crystallinity were formed on the Si crystal substrate.

[0034] Example 2 A platinum (Pt) metal film was formed as a conductive film on the single crystal film of the crystalline metal nitride in the same manner as in Example 1, except that nitrogen gas was used instead of oxygen gas. Then, the crystal substrate of the laminated structure, the single crystal film of the crystalline metal nitride, and the conductive film were each measured using an X-ray diffraction device. FIG. 13 shows the XRD measurement results. As is clear from FIG. 13, a (Hf, Zr)N film and a Pt single crystal film having good crystallinity were formed on the Si crystal substrate. When measured by a four-terminal method, the obtained single crystal film of the crystalline metal nitride had good conductivity.

[0035] The epitaxial film as the crystal obtained in the same manner as above was evaluated using metal particles at a temperature of 500°C, which is above the transformation temperature, to see whether dislocation or slip deformation due to stress occurs. The evaluation results are shown in Figure 11. As is clear from Figure 11, the example product showed superelasticity of 10% or more by being deformed at a temperature above the transformation temperature, and no dislocation or slip deformation occurred even when deformed, and had good shape memory properties.

[0036] The deposition apparatus used in Example 1 is shown in Fig. 14. The deposition apparatus in Fig. 14 includes at least metal sources 101a-101b in a crucible, earths 102a-102h, ICP electrodes 103a-103b, cut filters 104a-104b, DC power sources 105a-105b, RF power sources 106a-106b, lamps 107a-107b, Ar source 108, reactive gas source 109, power source 110, substrate holder 111, substrate 112, cut filter 113, ICP ring 114, vacuum chamber 115, and rotation shaft 116. The ICP electrodes 103a-103b in Fig. 14 have a substantially concave curved shape or a parabolic shape curved toward the center of substrate 112.

[0037] As shown in Fig. 14, the substrate 112 is fixed on the substrate holder 111. Next, the rotating shaft 116 is rotated using the power supply 110 and a rotating mechanism (not shown) to rotate the substrate 112. The substrate 112 is heated by the lamps 107a-107b, and the inside of the vacuum chamber 115 is evacuated to a vacuum or reduced pressure by a vacuum pump (not shown). Thereafter, Ar gas is introduced from the Ar source 108 into the vacuum chamber 115, and argon plasma is formed on the substrate 112 using the DC power supplies 105a-105b, the RF power supplies 106a-106b, the ICP electrodes 103a-103b, the cut filters 104a-104b, and the earths 102a-102h, thereby cleaning the surface of the substrate 112.

[0038] Ar gas is introduced into the vacuum chamber 115, and a reactive gas is introduced using a reactive gas source 109. At this time, lamps 107a to 107b, which are lamp heaters, are alternately turned on and off repeatedly, so that a crystal growth film of better quality can be formed.

[0039] The laminated structure obtained in the same manner as in Example 1 was subjected to STEM analysis. The results are shown in Figs. 15 to 17. From Fig. 15, it can be seen that an embedded layer 1004 is formed between the crystal substrate 1011 and the epitaxial layer 1001, and further, amorphous layers 1002 and 1003 are formed. From Fig. 16, it can be seen that the first amorphous layer 1002 on the crystal substrate 1011 contains Si of the crystal substrate and Zr, which is a constituent metal of the epitaxial layer 1001. From Fig. 17, it can be seen that the embedded layer 1004 has a cross-sectional shape of a substantially inverted triangle, and is an oxide containing Hf and Si.

[0040] (Examples) Examples of applications of the obtained laminated structure will be described in more detail below with reference to the drawings, but the present invention is not limited to these examples. In the present invention, unless otherwise specified, a piezoelectric device or the like can be manufactured from the laminated structure by using known means.

[0041] 9 shows an embodiment of an acoustic MEMS transducer constituting a MEMS microphone in which the laminated structure of the present invention is preferably used. The MEMS transducer can constitute an acoustic emission device (for example, a speaker, etc.).

[0042] The MEMS microphone composed of the acoustic MEMS transducer in FIG. 9 shows a cantilever type MEMS microphone, and includes a Si substrate 21 having two cantilever beams 28A, 28B and a cavity 30. Each of the cantilever beams 28A, 28B is fixed to the substrate 21 at each end, and a gap 9 is provided between the cantilever beams 8A, 8B. The cantilever beams 8A, 8B are formed by a laminated structure including, for example, a plurality of piezoelectric layers (PZT films) 26a, 26b, which are alternated with a plurality of electrode layers, i.e., Pt films 24a, 24b, 24c and SRO films 25a, 25b, 25c, 25d. A dielectric layer (single crystal film of crystalline oxide) 23 electrically insulates the cantilever beams 8A, 8B from the crystal substrate 21. In FIG. 9, a neutron absorbing material (e.g., HfO2 or its mixed crystal) is used for the dielectric layer (single crystal film of a crystalline oxide) 23, which has superior adhesion to the Si substrate and crystallinity compared to cases where SiO2, SiN, etc. are used, and furthermore, has superior piezoelectric properties and durability.

[0043] FIG. 10 shows an example of application to a fluid ejection device that can be used in printing applications, particularly in the form of an inkjet printhead, in which the laminated structure of the present invention is preferably used, and specifically shows a cross-sectional view of a portion of a wafer having a piezoelectric actuator including Pt films 34a, 34b and SRO films 35a, 35b as electrode layers and a PZT film 36 as a piezoelectric film. In addition to the piezoelectric actuator, the wafer of FIG. 10 also includes a chamber 41 for containing a fluid. The chamber 41 is configured to take in a fluid from a tank (not shown) through a flow path 40. The wafer of FIG. 10 also includes a Si substrate 31, on which a dielectric layer (single crystal film of a crystalline oxide) 33 is provided as a first epitaxial layer, facing the chamber 41. 10, a neutron absorbing material (e.g., HfO2 or its mixed crystal) is used for the dielectric layer (single crystal film of crystalline oxide) 23, which has superior adhesion to the Si substrate and crystallinity as well as superior piezoelectric properties and durability compared to the case of using SiO2, SiN, etc. Note that the single crystal film of crystalline oxide 33 has, for example, a quadrangular shape in a top view (not shown), and such a shape may be any of, for example, a square, a rectangle, a rectangle with rounded corners, a parallelogram, etc.

[0044] On the single crystal film 33 of the crystalline oxide, a Pt film 34a, an SRO film 35a, a piezoelectric film (PZT film) 36, an SRO film 35b, and a Pt film 34b are laminated in this order to form a piezoelectric actuator. The piezoelectric actuator further includes an insulating film 37 extending on the electrodes 34a and 35a, the piezoelectric film 36, and the electrodes 34b and 35b. The insulating film 37 includes a dielectric material used for electrical insulation, and such a dielectric material may be a known dielectric material, for example, a SiO2 layer, a SiN layer, or an Al2O3 layer. The thickness of the insulating layer including the insulating film as a constituent material is not particularly limited, but is preferably between about 10 nm and about 10 μm. The conductive path 39 is provided on the insulating layer (insulating film) 37 and contacts the electrodes 34a and 35a and the electrodes 34b and 35b, respectively, to enable selective access during use. The conductive path may be made of a known conductive material, and a suitable example of such a conductive material is aluminum (Al). The passivation layer 42 is provided on the insulating layer 37, the electrodes 34b and 35b, and the conductive path 39. The passivation layer 42 may be made of a dielectric material used for passivation of the piezoelectric actuator, and the dielectric material is not particularly limited and may be a known dielectric material. Suitable examples of the dielectric material include SiN and SiON (silicon oxynitrate). The thickness of the passivation layer is not particularly limited, but is preferably between about 0.1 μm and about 3 μm. The conductive pad 38 is also provided along the piezoelectric actuator and is electrically connected to the conductive path 39. The passivation layer 42 functions as a barrier layer that protects the piezoelectric body from moisture and the like. [Industrial Applicability]

[0045] The crystal and layered structure of the present invention are applicable to various applications, but are particularly suitable for use as buffer layers and crystal growth substrates, for example, in the manufacture of electronic devices for electronic equipment and sensor systems. [Explanation of symbols]

[0046] 1. Crystal Substrate 2. Oxide film 3 (First) Epitaxial Layer 4 Second epitaxial layer 5. Third epitaxial layer 6 Fourth epitaxial layer 11. Silicon substrate 13 Single crystal film of crystalline oxide 14 Conductive film 15 SRO membrane 16 PZT membrane 21 Crystalline substrate (Si substrate) 23 (First) epitaxial layer (single crystal film of crystalline oxide) 24a Second epitaxial layer (Pt film) 24b Sixth epitaxial layer (Pt film) 24c 10th epitaxial layer (Pt film) 25a Third epitaxial layer (SRO film) 25b Fifth epitaxial layer (SRO film) 25c Seventh epitaxial layer (SRO film) 25d 9th epitaxial layer (SRO film) 26a Fourth epitaxial layer (PZT film) 26b Eighth epitaxial layer (PZT film) 28A Cantilever Beam 28B Cantilever beam 29 Gap 30 cavities 31 Crystalline substrate (Si substrate) 33 (First) epitaxial layer (single crystal film of crystalline oxide) 34a Second epitaxial layer (Pt film) 34b Sixth epitaxial layer (Pt film) 35a Third epitaxial layer (SRO film) 35b Fifth epitaxial layer (SRO film) 36 Fourth epitaxial layer (PZT film) 37 Insulating Film 38 Conductive Pad 39 Conductive Path 40 Flow Path 41 Chamber 42 Passivation Layer 101a~101b Metal source 102a~102j Earth 103a~103b ICP electrode 104a~104b Cut Filter 105a~105b DC power supply 106a~106b RF power supply 107a~107b Lamps 108 Ar source 109 Reactive Gas Sources 110 Power supply 111 PCB Holder 112 Substrate 113 Cut Filter 114 ICP Ring 115 Vacuum chamber 116 Rotational Axis 1001 Epitaxial layer 1002 First amorphous layer 1003 Second amorphous layer 1004 Buried Layer 1011 Board

Claims

1. A laminated structure having at least a crystal substrate which is a Si substrate and an epitaxial film which is a metal oxide containing Hf and Zr, a first amorphous layer formed between the crystal substrate and the epitaxial film and containing Zr and Si; a second amorphous layer formed between the first amorphous layer and the epitaxial film, the second amorphous layer including Hf, Zr and Si; one or more buried layers embedded in a portion of the crystal substrate and containing Hf and Si; having the epitaxial film contains crystals that exhibit superelasticity of 10% or more by deformation at a transformation temperature or higher, The buried layer has a cross-sectional shape of a substantially inverted triangle.

2. A conductive film formed on the epitaxial film and made of Pt, a regular ridge-valley structure is provided at an interface between the epitaxial film and the conductive film; 2. The laminated structure according to claim 1, wherein the angles formed by adjacent vertices and bottoms of the peak-valley structure are different from each other within a range of 30° to 45°.

3. A laminated structure as described in claim 1, wherein a peak-valley structure is provided at the interface between the second amorphous layer and the epitaxial film.

4. An electronic device, electronic equipment, or system including a laminate structure, characterized in that the laminate structure is the laminate structure according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Forming method of dielectric film

    JP2004006960A

  • Formation method of insulation film

    JP2009158784A

  • Film structure and manufacturing method of the same

    JP2019216181A

  • Shape memory material

    JP2020097790A

  • Fe-BASED SHAPE MEMORY ALLOY MATERIAL AND METHOD FOR PRODUCING SAME

    WO2018047787A1